Characterization and Removal of Dissolved Organic Matter in River Water Through Preoxidation-Coagulation Process - Euis Nurul Hidayah; Grace Claudia Anastasia; Okik Hendriyanto Cahyonugroho (Universitas Andalas, 2019)
Dissolved organic matter (DOM), which is part of of natural organic matter or NOM, contained of carbon compound and can cause problems related to taste, odor, and disinfection by-products (DBPs) in water and treated water. Permanganate is strong oxidant and have been know its efficiency in oxidazing organic compound. Coagulation is most widely used in all water treatment plant due to its efficiency in removing suspended solid. The objectives of this study is to characterize and to remove natural organic matter in term of Â DOMÂ in water through KMnO4 preoxidation, Al2(SO4)3 or FeCl3 coagulation, KMnO4 preoxidation followed by Al2(SO4)3 or FeCl3 coagulation. Raw water, which was taken from Jagir River in Surabaya, and treated water were measured quantitatively by using total organic carbon (TOC), ultraviolet at wavelength 254 nm (UV254) in order to know its aromatic properties. In addition, fourier transfor m infrared spectroscopy (FTIR) was used to identify the functional group of DOM in water and treated water. The results showed that raw water has high TOC concentration (6,9 mg/L) and mainly composed of aromatic (UV254 0.075 cm-1). The optimum result showed that TOC concentration and UV254 removed significantly into 4,2 mg/L and 0,0020 cm-1, respectively after preoxidation followed by FeCl3 coagulation. According to FTIR analysis, mostly single bond carbon such as C-O and C-H still exist in treated water. This results indicated that preoxidation-coagulation has a better performance than preoxidation only and coagulation only.